MODERN MODELS OF SOCIAL MANAGEMENT TRANSFORMATION - Тетяна Кулініч; Олена Бакланова; Катерина Белоус (Економіка та суспільство)
The relevance of this article is driven by the need to study and develop models that enable economic entities to respond more effectively to the demands of modern society, promote human potential development, ensure social stability, and improve the quality of life for the population. The aim of this article is to comprehensively examine and analyze modern models of social management to understand which approaches are most effective in conditions of dynamic change. The research results demonstrate that modern models for transforming social management in enterprises are based on transformations involving various focal components, which ensure a comprehensive and effective strategy for achieving not only economic but also social objectives. Future research prospects involve a deeper analysis of the interaction between components of modern social management models and their impact on the sustainable development of enterprises in the context of global social and economic changes.